ADCY5 Mutations and Benign Hereditary Chorea - J. Gordon Millichap (Pediatric Neurology Briefs Publishers, 2015)
Investigators from the Institute of Neurology, London, UK, and centers in Italy, Germany, and Greece, studied 18 unrelated cases of benign hereditary chorea BHC (7 familial, 11 sporadic) who were negative for NKX2-1 mutations.